2019
DOI: 10.1073/pnas.1812092116
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of chloroplast retrograde signaling facilitates green plant adaptation to land

Abstract: Chloroplast retrograde signaling networks are vital for chloroplast biogenesis, operation, and signaling, including excess light and drought stress signaling. To date, retrograde signaling has been considered in the context of land plant adaptation, but not regarding the origin and evolution of signaling cascades linking chloroplast function to stomatal regulation. We show that key elements of the chloroplast retrograde signaling process, the nucleotide phosphatase (SAL1) and 3′-phosphoadenosine-5′-phosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 53 publications
4
124
0
Order By: Relevance
“…Light-induced metabolic adjustments, beyond photosynthetic carbon metabolism and other chloroplastic pathways, in turn remain poorly understood. Recently, Zhao et al (2019) demonstrated that a conserved signaling mechanism, where a chloroplast retrograde signal interacts with hormonal signaling to drive stomatal closure, is operational in angiosperms, mosses and ferns [48]. Our studies provide evidence that high-light-induced signals, likely originating from chloroplasts, are reflected by regulatory adjustments in SAHH at the level of complex formation and phosphorylation in both Physcomitrella and Arabidopsis (Fig 5A).…”
Section: Discussionsupporting
confidence: 62%
“…Light-induced metabolic adjustments, beyond photosynthetic carbon metabolism and other chloroplastic pathways, in turn remain poorly understood. Recently, Zhao et al (2019) demonstrated that a conserved signaling mechanism, where a chloroplast retrograde signal interacts with hormonal signaling to drive stomatal closure, is operational in angiosperms, mosses and ferns [48]. Our studies provide evidence that high-light-induced signals, likely originating from chloroplasts, are reflected by regulatory adjustments in SAHH at the level of complex formation and phosphorylation in both Physcomitrella and Arabidopsis (Fig 5A).…”
Section: Discussionsupporting
confidence: 62%
“…responses in which guard cell volume and hence stomatal aperture are driven by actively mediated changes in guard cell osmotic content). Seedless plants clearly possess actively mediated responses to light (Doi et al ., ), CO 2 (Franks & Britton‐Harper, ), and drought and high‐light stress (Zhao et al ., ), although the generality of active stomatal movements in some bryophytes remains unclear (Renzaglia et al ., ; Duckett & Pressel, ; Duckett et al ., ).…”
Section: New Ideas and New Evidence About Stomatal Responses To Watermentioning
confidence: 99%
“…Homologues of genes once thought to be restricted to embryophytes are now being detected in streptophyte algae. Examples include those involved in symbiotic or pathogenic interactions with soil microbes 4 , phytohormone signalling [5][6][7][8] , desiccation/stress 9 , plastid/nucleus retrograde signalling 10,11 and cell wall metabolism 12 . Importantly, many transcription factors (TFs) thought to be specific to embryophytes originated in streptophyte algae and also substantially expanded there 13 .…”
mentioning
confidence: 99%